2006
DOI: 10.21236/ada456046
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Detect Phishing Emails

Abstract: There are an increasing number of emails purporting to be from a trusted entity that attempt to deceive users into providing account or identity information, commonly known as "phishing" emails. Traditional spam filters are not adequately detecting these undesirable emails, and this causes problems for both consumers and businesses wishing to do business online. From a learning perspective, this is a challenging problem. At first glance, the problem appears to be a simple text classification problem, but the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(188 citation statements)
references
References 0 publications
1
182
0
5
Order By: Relevance
“…Phishing variables are selected from reviewing phishing related literature (Drake et al, 2005;Fett et al, 2006) For different analysis, different set of data was used. For factor analysis, five different phishing emails were shown to coders.…”
Section: Variables and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Phishing variables are selected from reviewing phishing related literature (Drake et al, 2005;Fett et al, 2006) For different analysis, different set of data was used. For factor analysis, five different phishing emails were shown to coders.…”
Section: Variables and Proceduresmentioning
confidence: 99%
“…Consequently, some studies identified phishing specific features and systems were designed accordingly. Some of the phishing specific features are IP-based URLs, age of domain names, non-matching URLs, number of links, number of domains, number of dots, and use of javascript (Drake, Oliver, & Koontz, 2005;Fett, Sadeh, & Tomasic, 2006). However, it can be argued that easily discernable features in text, in the same sense, can be easily manipulated by sophisticated attackers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus high accuracy from the data mining algorithms cannot be expected. However, the evidence supporting the golden nuggets comes from a number different algorithms and feature sets and we believe it is compelling [26].…”
Section: Mining E-banking Phishing Websites Challengesmentioning
confidence: 94%
“…Most commercial products works on the network level, where an email is inspected and a policy is applied. Various featurebased solutions [5], [6], [7], [8], [9] have been proposed to address the classical issues in email security, such as spam detection, phishing detection and email spoofing detection. The solutions base on term features that are extracted from email contents or sender features that describe the email sender's information.…”
Section: Related Workmentioning
confidence: 99%